2018
DOI: 10.3389/fimmu.2018.01868
|View full text |Cite
|
Sign up to set email alerts
|

Silent Witness: Dual-Species Transcriptomics Reveals Epithelial Immunological Quiescence to Helminth Larval Encounter and Fostered Larval Development

Abstract: Gastrointestinal nematodes are among the most prevalent parasites infecting humans and livestock worldwide. Infective larvae of the soil-transmitted nematode Ascaris spp. enter the host and start tissue migration by crossing the intestinal epithelial barrier. The initial interaction of the intestinal epithelium with the parasite, however, has received little attention. In a time-resolved interaction model of porcine intestinal epithelial cells (IPEC-J2) and infective Ascaris suum larvae, we addressed the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 95 publications
1
16
0
Order By: Relevance
“…Reports have shown that CHI3L1 is associated with many basic processes in highly conserved species including inflammation, cell apoptosis, tumor metabolism, or even in inflammatory chemotaxis. 34,[44][45][46] Here, we propose that CHI3L1 can exert a protective effect during IDD, and the mechanism of which is also conserved between human and mice. Since CHI3L1 is an endogenous factor, it can be a good therapeutic target in developing non-surgical treatment for IDD.…”
Section: Discussionmentioning
confidence: 86%
“…Reports have shown that CHI3L1 is associated with many basic processes in highly conserved species including inflammation, cell apoptosis, tumor metabolism, or even in inflammatory chemotaxis. 34,[44][45][46] Here, we propose that CHI3L1 can exert a protective effect during IDD, and the mechanism of which is also conserved between human and mice. Since CHI3L1 is an endogenous factor, it can be a good therapeutic target in developing non-surgical treatment for IDD.…”
Section: Discussionmentioning
confidence: 86%
“…Despite being a process with high adaptive cost for the parasite, it could confer evolutionary benefits in terms of establishment in the host, as it has been proposed for nematode parasites whose larvae undergo migrations that begin and end in the same location [5]. However, the molecular mechanisms governing L3 migration processes in ascariasis remain unclear [6,7]. For this reason, the knowledge of these key aspects of the life-cycle of the parasite could contribute to develop new intervention strategies in human and porcine ascariasis by studying the molecular basis of the host-parasite relationships [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanisms governing L3 migration processes in ascariasis remain unclear [6,7]. For this reason, the knowledge of these key aspects of the life-cycle of the parasite could contribute to develop new intervention strategies in human and porcine ascariasis by studying the molecular basis of the host-parasite relationships [7,8]. Thereby, the interaction between different species of pathogens and the fibrinolytic system of their corresponding host has already been studied [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Specific temporal regulation of certain virulence factors might also depend on their other putative functions and co-expression networks. For instance, hyaluronidase, a hydrolytic enzyme that degrades the glycosaminoglycan hyaluronic acid, erected as crucial for pathogenesis of Ancylostoma caninum , Anisakis simplex and A. suum (Hotez et al, 1994; Wang, 2014; Ebner et al, 2018) showed no differential regulation in either of hosts studied herein, albeit expressed in the transcriptome. Rhoads et al (2001) noted its release in A. suum when transitioning from L3 to L4, corroborating its other important functions next to facilitation of larval penetration, such as feeding, proper molting and development.…”
Section: Discussionmentioning
confidence: 86%
“…Aspartic protease 6 is an endopeptidase involved in haemoglobin digestion, tissue penetration or host-derived nutrient digestion in helminths (Koehler et al, 2007; Ebner et al 2018). The importance of proteases and protease inhibitors for helminths is reflected in their vast representation in nematode and platyhelminth species, as noted in a large comparative genomic study of parasitic worms (Coghlan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%